The Representation of Italy in Caterina Edwards’ The Sicilian Wife and Rita Ciresi’s Sometimes I Dream in Italian - Cesari, Maria Giuseppina (Giusy) (Italian Canadiana, 2020)
This paper wishes to explore how Caterina Edwards, an Italian Canadian writer, and Rita Ciresi, an Italian American writer, share a strong, although very different, personal and authorial relation to Italy and the Italian language. I shall be focusing on their similarities rather than differences: they are brought up in North America, their mother tongue is English, they (and their characters) travel from/to Sicily, Venice, Edmonton as well as New Haven, Venice and Rome in a complex chronotopic framework. Old and new myths, mystery and parody are intertwined in their innovative texts. These “new travelers” are part of a new cross-border literary community where Italy plays a significant role as much as their countries of origin, Canada and the US. Is Italy a place to visit, a crime scene, a mythical land, a country of passionate desire, or... just a dream?